Appliсation of the phase correlation algorithm and its extension in the optical stabilizer of unmanned aerial vehicles - Dreval, O.L.; Doroshenko, А.Yu. (PROBLEMS IN PROGRAMMING, 2018)
The use of the phase correlation algorithm as the basis of unmanned aerial vehicles (UAV) Optical Stabilizer on purpose to determine the displacement of the housing relative to the surface is described. Also, the possibility of application of the phase correlation algorithm extensions to increase accuracy and reduce computing costs is considered. The algorithm implementation in bot MATLAB language and C is provided. The computational complexity of the algorithm implementation in C was experimentally analyzed in the scope of embedded systems. The proposed algorithm gives not only an auxiliary possibility to stabilize the aircraft position but also to calculate absolute position of the aircraft in space.Problems in programming 2017; 1: 111-119